1951
DOI: 10.1002/zaac.19512650415
|View full text |Cite
|
Sign up to set email alerts
|

Über Das Dischwefeltrioxyd

Abstract: Schwefel verbindet sich leicht mit SO3 zu (S2O3)x. S2O3 ist sehr unbeständig; es kann in S und SO3, aber auch vollständig in S und SO2 zerfallen. Bei der Solvolyse liefert S2O3 weder Dithionit (oder Sulfoxylat) noch Polythionat. Seinen Eigenschaften nach gehört (S2O3)x in die Reihe der Stoffe, wie z. B. Pyridin →SO3, Amin→SO3, die nach Baumgarten dadurch zustande kommen, daß sich ein Reagens mit einem freien Elektronenpaar in die Oktettlücke der ebenen SO3‐Molekel einlagert. S2O3 ist von allen bisher bekannten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
11

Year Published

1965
1965
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
0
20
0
11
Order By: Relevance
“…In a similar manner, other cyclic trimers were prepared in high to excellent yields, except for 3c which provided 7c in only 56% yield due to the steric effect of tertiary butyl group (Scheme 5). This phenomenon is reminiscent of the observations made by Appel who reported that the products of 1,3-dilopar cycloaddition of phosphaalkenes with azides could eliminate nitrogen to give the dimer diazadiphosphetidines as final products [17]. The same thing happens if the reaction is carried out in dry benzene, affording also the cyclic trimers.…”
Section: Resultsmentioning
confidence: 56%
“…In a similar manner, other cyclic trimers were prepared in high to excellent yields, except for 3c which provided 7c in only 56% yield due to the steric effect of tertiary butyl group (Scheme 5). This phenomenon is reminiscent of the observations made by Appel who reported that the products of 1,3-dilopar cycloaddition of phosphaalkenes with azides could eliminate nitrogen to give the dimer diazadiphosphetidines as final products [17]. The same thing happens if the reaction is carried out in dry benzene, affording also the cyclic trimers.…”
Section: Resultsmentioning
confidence: 56%
“…[16] The regioselective [2+2] cyclodimerization of phosphaalkenes is well-established, and affords either the head-totail (i.e., 1,3-diphosphetane) or the head-to-head product (i.e., 1,2-diphosphetane). [16,20,[22][23][24][25][26][27][28][29][30][31][32][33][34] Dimer 2a was fully characterized by using 31 P, 1 H and 13 C{ 1 H} NMR spectroscopy, mass spectrometry and elemental analysis. The molecular structure of 2a, shown in Figure 3, reveals that the sterically favorable anti-configuration of the adjacent P-Ph moieties is adopted.…”
Section: Php=cph 2 (1a)mentioning
confidence: 99%
“…The metrical parameters are quite similar to those discussed previously for 1,2-[AdP-CPh 2 ] 2 [20] and related compounds having 1,2-P 2 C 2 rings. [30,[36][37][38][39][40] The P-C Ph2 bonds [P(1)-C(7): 1.959(3) Å, P(2)-C(26): 1.937(3) Å] are longer than a typical P-C single bond (1.85 Å). Likewise, the C Ph2 -C Ph2 bond length [C(7)-C(26): 1.614(4) Å] is longer than a typical C-C single bond (1.53 Å).…”
Section: Php=cph 2 (1a)mentioning
confidence: 99%
“…Under the literature conditions [24] designed for aziridine formation, the chloride ( 3 -2 1 was produced almost quantitatively after 16 h at room temperature by treatment of the hydrazino alcohol 20 with triphenylphosphane, CC14 and triethylamine in acetonitrile. Conversion of 20 in CCI4 solvent[25] required 2 equiv.…”
Section: N'-(2-chloroethyl)-26-diisopropylacetophenone Hydrazone (21)mentioning
confidence: 99%